Object–based learning and history teaching: the role of emotion and empathy in engaging students with the past. Issue 1 (2nd January 2021) - Ellinghaus, Katherine; Marsden, Beth; McIlvenna, Una; Moore, Fiona; Spinks, Jennifer
Abstract: In 2017 and 2018 historians teaching at the University of Melbourne, in collaboration with staff from the University of Melbourne's Cultural Collections, brought an element of object-based learning to their undergraduate teaching. This article describes their pedagogical strategies in bringing material culture to a study of the past, discusses the advantages to this kind of teaching, and describes the results of a survey of students which aimed to measure student engagement and skills gained. We argue that object-based learning is an adaptable pedagogy that allows students to feel confident in reading a variety of historical sources, extrapolate about the experiences and emotions of people in the past and to think deeply about the politicised ways in which societies commemorate, memorialise and archive the past.